Counter-Radicalization through Problem Based Learning in the Perspective of the Al Qur'an - Sarnoto, Ahmad Zain; Burhanuddin, Nandang (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This study departs from the problem of the increasing violence of movements in the name of religion in the world of education, especially schools and pesantren. The perpetrators were not only students but also teachers and those closest to the students. Infiltration is not only in face-to-face "mission religion" (al-mujawwahah) but has infiltrated textbooks and curriculum scattered throughout the country. Various studies and expert statements that indicate a weak curriculum, inadequate transfer of knowledge among educators, ignorance, and misinterpretation of the verses of the Al-Qur’an regarding radicalism, especially those that lead to acts of terrorism and the like in schools, are getting stronger. The ISIS groups, Al-Qaeda, Jamaah Islamiyah, Laskar Jihad, MMI, the Islamic State of Indonesia (NII), and so on have become the main recruiters of students in Indonesia. As a religio-political construction, radicalism is a consensus and is built deliberately to destroy the Islamic world order, targeting vulnerable children who are still looking for self-identity. Therefore, a comprehensive, systematic, methodological, and analytical approach to learning based on Al-Qur'an and hadith is needed by educators and their students, through problem-based learning. The PBL approach is an educational approach to learning and is in accordance with the content of the Qur'an which emphasizes rahmatan lil'alamin, justice (adl), qawdah al hasanah, deliberation, and samahah. Although, the mufasirs and scholars have different opinions regarding the concept of rahmatan lil 'alamin and justice in education, generally for mankind, their thoughts are very significant as a milestone and source of knowledge, both ontologically, epistemologically, and axiologically for the content and implementation of based learning. problem (PBL) for efforts to counter radicalization in the world of education in Indonesia, especially the world.